Emotional Intelligence and Wellbeing a Study of College Students (Indian Journal of Psychology & Education, 2016)
The present study is an attempt to study the relationship between emotional intelligence and wellbeing of adolescent. The study was conducted on a sample of 100 girl college students of Karnal (Haryana). Emotional intelligence scale and wellbeing measures were used to collect the data. Pearson product moment coefficient of correlation was employed in order to find out the relationship between emotional intelligence and wellbeing among adolescent girls. Results showed that emotional intelligence is positively correlated with wellbeing. The paper concludes with a discussion of the implications of these findings together with limitations of the study and avenues for future research.